Associations of Alcohol Availability and Neighborhood Socioeconomic Characteristics With Drinking: Cross-Sectional Results From the Multi-Ethnic Study of Atherosclerosis (MESA). (15th October 2015) - Brenner, Allison B.; Diez Roux, Ana V.; Barrientos-Gutierrez, Tonatiuh; Borrell, Luisa N.
Abstract : Background : Living in neighborhoods with a high density of alcohol outlets and socioeconomic disadvantage may increase residents' alcohol use. Few researchers have studied these exposures in relation to multiple types of alcohol use, including beverage-specific consumption, and how individual demographic factors influence these relationships. Objective : To examine the relationships of alcohol outlet density and neighborhood disadvantage with alcohol consumption, and to investigate differences in these associations by race/ethnicity and income. Methods : Using cross-sectional data ( N = 5, 873) from the Multi-ethnic Study of Atherosclerosis in 2002, we examine associations of residential alcohol outlet density and neighborhood socioeconomic disadvantage with current, total weekly and heaviest daily alcohol use in gender-specific regression models, as well as moderation by race/ethnicity and income. Results : Drinking men living near high densities of alcohol outlets had 23%–29% more weekly alcohol use than men in low density areas. Among women who drank, those living near a moderate density of alcohol outlets consumed approximately 40% less liquor each week than those in low density areas, but higher outlet densities were associated with more wine consumption (35%–49%). Living in highly or moderately disadvantaged neighborhoods was associated with a lower probability of being a current drinker, but with higher rates of weekly beer consumption. Income moderated the relationship between neighborhood context and weekly alcohol use. Conclusions/Importance : Neighborhood disadvantage and alcohol outlet density may influence alcohol use with effects varying by gender and income. Results from this research may help target interventions and policy to groups most at risk for greater weekly consumption.